Kajian Nilai “Satyam” Dalam Film “Snowden” (Sebuah Analisis Semiotika Roland Barthes) - I Made Bagus Andi Purnomo (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2020)
Very rapid development of the era resulted in education not only limited to class meetings. But also penetrated the digital world. The main community of the young generation is very fond of learning through social media. Starting from google, youtube, movies and also various other digital references. However, not all digital facilities, one of which is film that provides educational content that is able to have an impact on changing the character of the younger generation to the better. Mostly only love films and even penetrated in films that should not have been watched by children (sexuality). On this basis, this research was conducted to examine one of the films in the public spotlight namely the film "Snowden".The method used in the research is descriptive qualitative with the approach of study aimed at interpreting and interpreting culture so that readers can understand in the form of meaningful texts. The object of research is the film "Snowden". The theory used in this research is the theory of semiotics which is to examine the symbols, signs and visual meanings in film. Charles Sanders Peirce. Meanwhile the data analysis method uses the Miles and Huberman methods. This research will produce a study of moral values in the film "Snowden".Keywords: Value, Satyam, Film, Snowden